2014
DOI: 10.17017/jfish.v2i3.2014.57
|View full text |Cite
|
Sign up to set email alerts
|

Record of the largest longtail tuna, Thunnus tonggol (Bleeker 1851) from off shore Salalah in the Sultanate of Oman

Abstract: Capture of a great Longtail tuna, Thunnus tonggol from off Shore of the city of Salalah, Arabian Sea, Sultanate of Oman in January 2013 is described in this paper. Its morphometric and meristic characters are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Yesaki (1982) reported size group differences in distribution with respect to inner and outer neritic regime along the Phuket coast. Progressive increase in mean length of LOT along the eastern Arabian Sea starting from the south-west coast (50 cm) through the north-west coast of India (61.9 cm) to the Gulf of Oman (74 cm) was reported by Kaymaran et al, 2011 andAbdussamad et al (2012) and the largest captured LOT (142 mm) was caught off Salalah, Oman (Al-Mamari et al, 2014).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Yesaki (1982) reported size group differences in distribution with respect to inner and outer neritic regime along the Phuket coast. Progressive increase in mean length of LOT along the eastern Arabian Sea starting from the south-west coast (50 cm) through the north-west coast of India (61.9 cm) to the Gulf of Oman (74 cm) was reported by Kaymaran et al, 2011 andAbdussamad et al (2012) and the largest captured LOT (142 mm) was caught off Salalah, Oman (Al-Mamari et al, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…A recent study on the biology of the species in this region (Mohammed Koya et al, 2018) also revealed that the spawning peaked in May-June. The hooking of the largest LOT off Salalah, Oman (Al-Mamari et al, 2014) indicated the availability of large fishes in deeper waters of the northern AS. Hence, it may be construed that the mature fishes move to the deeper waters in the oceanic realm probably for further gonadal development and spawning.…”
Section: Discussionmentioning
confidence: 99%
“…Thunnus tonggol, known as Ikan Tongkol by local (Figure 2) is a commercially important pelagic species that found abundantly in tropical to temperate neritic habitat throughout the Indo-Pacific [6] [7]. It can reach a maximum length of 1.5 meters and up to 32 kilograms in weight [8] [9]. The lower side and belly are of silvery-white colour, with colourless elongate oval spots arranged in horizontally oriented rows [10] [11].…”
Section: Introductionmentioning
confidence: 99%